Transformasi Digital dalam Pembelajaran Pendidikan Agama Islam: Peluang dan Tantangan di Era Kecerdasan Buatan - Saputro, Ramanda Gian (Action Research Literate, 2025)
The development of digital technology has brought significant changes to the education sector, including Islamic Religious Education (PAI). The use of Artificial Intelligence (AI) presents great opportunities to enhance the effectiveness, interactivity, and flexibility of the learning process. Through digital innovation, teachers and students can access broader and more engaging learning resources. However, this transformation also presents new challenges, such as the misuse of technology, weak digital literacy, and the potential decline in spiritual interaction between teachers and students. Therefore, Islamic educators must wisely adapt to technological advancements while maintaining Islamic values as the foundation of all digital learning processes.